A study of novel harmonic indices in nanocones CNCk[n]. (3rd October 2019) - Mousavi, Seyed Farid; Gilani, Alireza; Alaeiyan, Mehdi
Abstract: The harmonic index for connected simple graph G = ( V, E ) is defined as, where Qu is a unique parameter which is acquired from vertex u ∈ V ( G ). By this index, six other types of indices called novel harmonic indices are defined. The first kind of these indices was studied by Zhong by considering Qu to be the degree of the vertex 2 as follow: The fifth type of this class can be defined by considering Qx to be the Su := ∑ v ∈ N ( u ) deg ( v ) as follows: . In this paper, we will compute some Novel harmonic indices of nonocones.